Efektivitas dan kontribusi penerimaan pajak hotel terhadap pendapatan asli daerah kota Makassar tahun (2015-2019) - Risa Rukmana; Raodatul Jannah; Nurlaila Hasmi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
The purpose of this study is to determine the effectiveness and contribution of hotel taxes to local revenue at the Office of the Regional Revenue Service of Makassar City. The type of data used is qualitative data and quantitative data. The data sources used are primary and secondary data. Methods of data collection using interviews and observations related to research. The research was analyzed using quantitative descriptive analysis method. The result of the research is that the level of effectiveness and contribution of hotel taxes in 2015-2019 can be said to be